2009
DOI: 10.1182/blood-2008-11-188458
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal responsiveness to interleukin-12 and interferon-α specifies human CD8+ effector versus central memory T-cell fates

Abstract: IntroductionCD8 ϩ T cells are critical mediators of adaptive inflammatory responses to intracellular pathogens. They require a series of signals for efficient expansion and acquisition of effector functions, such as cytokine secretion and lytic activity. These signals are delivered by professional antigen-presenting cells (APC) and include antigen recognition (signal 1), costimulatory activation (signal 2), and signaling provided by innate inflammatory cytokines (signal 3). 1 Whereas signals 1 and 2 prime naiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
64
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 46 publications
5
64
1
Order By: Relevance
“…We and others have shown that IL-12 and IFN-a also act directly on human naive CD8 T cells promoting the proliferation whereas favoring the acquisition of effector functions (25,26). However, there is scant information about the effects of innate inflammatory cytokines on the differentiation of human naive CD8 T cells into effector or memory CTLs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that IL-12 and IFN-a also act directly on human naive CD8 T cells promoting the proliferation whereas favoring the acquisition of effector functions (25,26). However, there is scant information about the effects of innate inflammatory cytokines on the differentiation of human naive CD8 T cells into effector or memory CTLs.…”
mentioning
confidence: 99%
“…However, there is scant information about the effects of innate inflammatory cytokines on the differentiation of human naive CD8 T cells into effector or memory CTLs. Previous data from Farrar's group suggest that IL-12 and IFN-a behave as nonredundant signals that differentially regulate the development of memory CTLs with T effector memory cell (TEM; CD62L low CCR7l ow ) or T central memory cell (TCM; CD62L hi CCR7 hi ) phenotypes, respectively (25). Frequently, specific surface markers have been used to ascribe functional attributes to memory CTLs, but phenotype cannot be directly translated into functional properties (27).…”
mentioning
confidence: 99%
“…Further, in human, both Eomes and T-bet are regulated by IL-12 in CD8 ϩ and CD4 ϩ T cells, respectively. 18,26,37 As such, it is unclear how the IL-12 signaling pathway regulates only one of the 2 transcription factors in each cell type and whether species differences can account for this regulation.In addition to Eomes, this analysis revealed 4 additional unique IL-12-induced intracellular regulators that were expressed in T EM in vivo. First, we identified both a dual-specificity phosphatase (DUSP5) and a MAP kinase (MAP3K8), both of which have been implicated in directly regulating effector T-cell activity.…”
mentioning
confidence: 99%
“…5,19 Our previous studies defined unique roles for IL-12 and IFN-␣/␤ in regulating effector and memory functions in both human CD4 ϩ and CD8 ϩ T cells. 18,26 Although IL-12 was unique in its ability to regulate effector cell commitment, the downstream targets of IL-12 that mediate this activity have not been elucidated. In the current study, we used a hypothesis-driven approach to dissect IL-12-driven gene expression pathways governing human CD8 ϩ T effector cell development.…”
mentioning
confidence: 99%
See 1 more Smart Citation